The Prevalence of Rifampicin Resistance in Mycobacterium Tuberculosis Patients Using Genexpert in Tertiary Medical College and Hospital (The Planet, 2022)
Objective:In this study our main goal is to evaluate rifampicin resistance in mycobacterium tuberculosis using GeneXpert in tertiary Medical College and Hospital. Method: This cross-sectional study was done at tertiary medical college and hospital atDhaka from November 2020 to April 2021, where 60clinically suspected or documented tuberculosis cases were selected as a sample population. Results: During the study, more than fifty percent (56.0%) of the patients were in the age group 20-40 years and 52% were male. About 35% of the patients had history of smoking. 13% patients delayed their treatment to initiate greater than 30 days and 8% cases treatment was incomplete. According to prevalence of drug resistance, results show that 5% Rifampicin (RIF) resistant cases detected by GeneXpert MTB/RIF were phenotypically confirmed as DR strains. Besides that, majority resistance cases were found in male, 66.7%. Conclusion: From our study we can say that, the emergence of drug resistance in TB poses a significant threat to TB control activities throughout the world. Xpert MTB/high RIF's sensitivity and specificity for RIF resistance detection support its use as an initial diagnostic test for RIF resistance. As a result, implementing molecular approaches for direct diagnosis of DRTB as part of routine analysis in health care institutions' laboratories would be extremely beneficial in adapting treatment regimens and limiting the spread of DR TB strains.
Keywords: Drug resistance (DR); tuberculosis (TB); multiple drug resistance (MDR)